The normalizing efficacy of Roselle (Hibiscus sabdariffa), Moringa (Moringa oleifera), Ginger (Zingiber officinale) and 'Ugwu' (Telfairia occidentalis) in the liver enzymes of wild rats (Rattus rattus) living around a cement plant ... : فعالية تطبيع الكركديه (الكركديه sabdariffa)، المورينجا (المورينجا أوليفيرا)، الزنجبيل (الزنجبيل officinale) و 'Ugwu' (Telfairia Occidentalis) في إنزيمات الكبد من الفئران البرية (الجرذ الجرذ) الذين يعيشون حول مصنع الأسمنت ... - Tajudeen Yahaya; Joy Okpuzor (OpenAlex, 2013)
The normalizing efficacy of roselle ( H. sabdariffa ), moringa ( M. oleifera ), ginger ( Z. officinale ) and 'ugwu' ( T. occidentalis ) in the liver enzymes of cement-dust exposed wild rats was evaluated. The rats were placed into seven groups, comprising 15 rats per group. Group one was tagged control 1, and rats in this group were unexposed. Group two was tagged control 2 and, together with groups three through seven, consisted of exposed rats. The ALT, AST and ALP levels in the rats were measured using standard protocols, before and after feeding the rats with 400 mg kg -1 ethanolic extracts of roselle, moringa, ginger, 'ugwu' and a mixture of the plant extracts, respectively, for 180 days. The % ALT decrease in the control 1 and 2 rats that received distilled water only were 4 and 17 respectively, whereas the % ALT decrease in the rats fed with roselle, moringa, ginger, 'ugwu' and mixture are 35.0, 45.0, 55.0, 50.0 and 62.0, respectively. The % decrease in the levels of AST in the control 1 and 2 rats ... : تم تقييم فعالية تطبيع الكركديه ( H. sabdariffa ) والمورينجا ( M. oleifera ) والزنجبيل ( Z. officinale ) و "ugwu" ( T. occidentalis ) في إنزيمات الكبد للفئران البرية المعرضة لغبار الأسمنت. تم وضع الفئران في سبع مجموعات، تضم 15 فأرًا لكل مجموعة. تم وضع علامة على المجموعة الأولى تحت عنصر التحكم 1، وكانت الفئران في هذه المجموعة غير معرضة للخطر. تم تمييز المجموعة الثانية بعلامة التحكم 2، وتألفت مع المجموعات من ثلاثة إلى سبعة من الفئران المكشوفة. تم قياس مستويات ALT و AST و ALP في الفئران باستخدام البروتوكولات القياسية، قبل وبعد إطعام الفئران بمستخلصات إيثانولية 400 مجم - 1 كجم من الكركديه والمورينجا والزنجبيل و "ugwu" ومزيج من المستخلصات النباتية، على التوالي، لمدة 180 يومًا. كانت النسبة المئوية للانخفاض في الفئران الضابطة 1 و 2 التي تلقت الماء المقطر فقط 4 و 17 على التوالي، في حين أن النسبة المئوية للانخفاض في الفئران التي تغذت على الكركديه والمورينجا والزنجبيل و "ugwu" والمزيج هي 35.0 و 45.0 و 55.0 و 50.0 و 62.0 على التوالي. كانت النسبة المئوية للانخفاض في مستويات AST في الفئران الضابطة 1 و 2 5 و 17 على ...